Gβ Regulates Coupling between Actin Oscillators for Cell Polarity and Directional Migration - Hoeller, Oliver; Toettcher, Jared E.; Cai, Huaqing; Sun, Yaohui; Huang, Chuan-Hsiang; Freyre, Mariel; Zhao, Min; Devreotes, Peter N.; Weiner, Orion D. (PLOS Biology, 2016)
Coupling of individual oscillators regulates biological functions ranging from crickets chirping in unison to the coordination of pacemaker cells of the heart. This study finds that a similar concept—coupling between actin oscillators—is at work within single slime mold cells to establish polarity and guide their direction of migration.